2003
DOI: 10.1097/01.brs.0000048644.91330.14
|View full text |Cite
|
Sign up to set email alerts
|

Simple Carrier Matrix Modifications Can Enhance Delivery of Recombinant Human Bone Morphogenetic Protein-2 for Posterolateral Spine Fusion

Abstract: The addition of either 15:85 BCP granules or allograft bone chips to the existing resorbable collagen sponge matrix enhanced delivery of rhBMP-2 in the posterolateral spine. The combination matrices were more compression resistant and had improved radiographic resorption properties that permitted easy radiographic visualization of new bone. In addition, a lower dose of rhBMP-2 (3 mg/side) was successful compared with the dose previously used with the plain collagen sponge (6 mg/side).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 23 publications
3
70
1
1
Order By: Relevance
“…To manufacture an osteoinductive artificial bone graft substitute, cytokines retaining osteoinductive activity (e.g., BMPs) have been combined with collagen and used to obtain spinal fusion in experimental animals or in human cases [1,4,5,17,25,26,35,36]. This experimental study was designed to achieve solid posterior interspinous lumbar fusion more effectively and less invasively than before with proper use of rhBMP-2 in combination with synthetic carrier materials.…”
Section: Discussionmentioning
confidence: 99%
“…To manufacture an osteoinductive artificial bone graft substitute, cytokines retaining osteoinductive activity (e.g., BMPs) have been combined with collagen and used to obtain spinal fusion in experimental animals or in human cases [1,4,5,17,25,26,35,36]. This experimental study was designed to achieve solid posterior interspinous lumbar fusion more effectively and less invasively than before with proper use of rhBMP-2 in combination with synthetic carrier materials.…”
Section: Discussionmentioning
confidence: 99%
“…9,43 Pre-clinical studies have also suggested that because of its favorable binding properties to osteoinductive growth factors such as rhBMP-2, the dose required to achieve successful bony fusion is effectively reduced. 44,45 To this end, recent studies have demonstrated that a 10-15% hydroxyapatite composition in a ceramic carrier is ideal for stem cell adhesion and osteoblastic differentiation. 46,47 In comparison, Grafton 1 is a DBM processed from human tissue into bone fibers combined with glycerol (79-85% content) to achieve a putty-like consistency.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results suggest that male rat BMSCs, which were xenogenically transplanted into the posterolateral lumbar spine of female rabbits, successfully survived without immune suppression. The CRM has been demonstrated to be an effective osteoconductive material in previous spine fusion study [1]. We therefore used CRM as a carrier of xenogenic BMSCs in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A compression resistant matrix (CRM, Medtronic Sofamor Danek, USA) used in this study was chemically composed of 15% hydroxyapatite (HA) and 85% b-tricalcium phosphate (b-TCP) with 500 lm average pore size and 80% porosity [1]. Aliquots of BMSCs (1 9 10 6 cells) were incubated with 5 cc CRM matrix in 25 T culture flask for 2 h to allow attachment; 32 female New Zealand rabbits (3.5-4 kg) were divided into two groups in this study.…”
Section: Implantation Of Bmscs Loaded Onto Crmmentioning
confidence: 99%